A three-dimensional forward dynamic model of the golf swing optimized for ball carry distance. Issue 4 (December 2016) - Balzerson, Daniel; Banerjee, Joydeep; McPhee, John
Abstract A 3D predictive golfer model can be a valuable tool for investigating the golf swing and designing new clubs. A forward dynamic model, which includes a four degree of freedom golfer model, a flexible shaft based on Rayleigh beam theory, an impulse-momentum impact model and a spin rate dependent aerodynamic ball model, is presented. The input torques for the golfer model are provided by parameterized joint torque generators that have been designed to mimic muscle torque production. These joint torques are optimized to create swings and launch conditions that maximize carry distance. The flexible shaft model allows for continuous bending in the transverse directions, axial twisting of the club and variable shaft stiffness as a function of the length. The completed four-part model with the default parameters is used to estimate the ball carry of a golf swing using a particular club. This model will be useful for experimenting with club design parameters to predict their effect on the ball trajectory and carry distance.